Eléments pour l’élaboration d’un manuel de littérature basque pour les collèges et lycées - Jean Casenave (Lengas, 2018)
The Basque language has been taught in secondary schools for more than thirty years. Today, it is widely taught in bilingual classes in “linguistic immersion” and “in schedule parity”, in all the current Basque-speaking area (Basque Autonomous Community, Basque zone of the “Pyrénées Atlantiques” department, northern part of the Foral Community of Navarra).Yet, for the northern part of the Basque Country (French Basque Country), there still isn’t today any literature book for secondary school students. This lack is regularly underlined by the different partners of the Basque language teaching system and the subjects taught in the Basque language: pupils, teachers, representatives of the French national school system and members of the Inspectorate, outside observers. Undeniably, it is possible to explain this deficiency with practical reasons in connection with the weakness of the supervisory structures of the Basque teaching system, notably in terms of the educational support of teachers. However, there are other reasons which may also explain – partially – the fact that up to now, no attempt to publish a book has been achieved. The most important is historiographical. It is about the periodisation pattern to adopt within the frame of the Basque literature. The question is also relevant for the Breton, Corsican or Occitan fields and, in these cases, it is mainly about the link between our literary works and the history of the French literature, its chronology and its historiographical choices. For the Basque and Catalan literatures, for example, the difficulty is increased by the fact that the literary production, in this respect, has to be taken into account on both sides of the Pyrenees, in the whole of the Basque and Catalan speaking areas. That means taking into account two different historical, sociological and cultural perspectives. To the question of periodisation, the choice of written corpora is to be added and especially, within them, the extent works from the popular tradition should have.